2016
DOI: 10.3390/ma9040241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn Content in a CuSnZn Metal Precursor on Formation of MoSe2 Film during Selenization in Se+SnSe Vapor

Abstract: The preparation of Cu2ZnSnSe4 (CZTSe) thin films by the selenization of an electrodeposited copper–tin–zinc (CuSnZn) precursor with various Sn contents in low-pressure Se+SnSex vapor was studied. Scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS) measurements revealed that the Sn content of the precursor that is used in selenization in a low-pressure Se+SnSex vapor atmosphere only slightly affects the elemental composition of the formed CZTSe films. However, the Sn content of the precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The altered composition and elemental abundance within the precursor thin films can strongly affect CZTSSe pathway formation. The Sn-poor samples with rich Cu and Zn compositions may have consumed the formation of secondary phases, such as Sn­(S,Se) 2 , during the annealing process by intermediate reactions (reactions and ), which ease the formation of the pure kesterite phase . Further, increased amounts of the excess Sn content in the precursor thin films might precipitate as Sn-based secondary phase Sn­(S,Se) 2 . …”
Section: Resultsmentioning
confidence: 99%
“…The altered composition and elemental abundance within the precursor thin films can strongly affect CZTSSe pathway formation. The Sn-poor samples with rich Cu and Zn compositions may have consumed the formation of secondary phases, such as Sn­(S,Se) 2 , during the annealing process by intermediate reactions (reactions and ), which ease the formation of the pure kesterite phase . Further, increased amounts of the excess Sn content in the precursor thin films might precipitate as Sn-based secondary phase Sn­(S,Se) 2 . …”
Section: Resultsmentioning
confidence: 99%
“…The excessive selenization of Mo should be avoided as it causes delamination of the back electrode from a substrate due to the significant volume expansion by the transformation from Mo to MoSe 2 (almost four times) [ 30 , 31 ]. In contrast, the formation of a thin layer of MoSe 2 should have a beneficial effect on the adhesion of the CZTSe absorber to the Mo back electrode and the semiconductor/metal contact, which changes from a Schottky (CZTSe-Mo) to Ohmic type (CZTSe-MoSe 2 -Mo), thereby reducing the barrier of the hole transfer [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…1). According to Yao et al (2016), the MoSe 2 layer forms at the CZTSe/Mo interface when the metal precursor of the CZTSe films contains excess Sn and the SnSe-or/ and SnSe 2 -containing phase in the CZTSe thin films may have catalyzed the formation of MoSe 2 layer. Taking this into consideration, it can be concluded that the TaSe 2 layer have similar formation features at the CZTSe/Ta interface in the CZTSe thin films depending on the Sn content.…”
Section: X-ray Diffractionmentioning
confidence: 99%